1989
DOI: 10.1128/aem.55.12.3113-3118.1989
|View full text |Cite
|
Sign up to set email alerts
|

In vivo protocol for testing efficacy of hand-washing agents against viruses and bacteria: experiments with rotavirus and Escherichia coli

Abstract: Ten antiseptic formulations, an unmedicated liquid soap, and tap water alone were compared for their capacities to eliminate human rotavirus from the finger pads of adult volunteers; three of the antiseptics, the soap, and the tap water alone were also tested against Escherichia coli. A fecal suspension of virus or bacterium was placed on each finger pad and air dried. The contaminated site was exposed to the test product for 10 s, rinsed in tap water, and dried on a paper towel. The residual virus or bacteriu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(63 citation statements)
references
References 29 publications
6
56
1
Order By: Relevance
“…The protective role of hand hygiene (and the dose-response effect) was also observed when hospital and PHC controls were analysed separately. This corresponds with studies that document the survivability of the influenza virus on nonporous surfaces for at least 24 hours and the possibility of contaminating hands and generating new infections (Ansari et al, 1989;Bean et al, 1982;Bell and World Health Organization Writing Group, 2006b), and also with studies that show that hand washing with soap and water is effective in removing pathogens from the surface of the hands (Larson et al, 2003;Luby et al, 2001).…”
Section: Discussionsupporting
confidence: 59%
“…The protective role of hand hygiene (and the dose-response effect) was also observed when hospital and PHC controls were analysed separately. This corresponds with studies that document the survivability of the influenza virus on nonporous surfaces for at least 24 hours and the possibility of contaminating hands and generating new infections (Ansari et al, 1989;Bean et al, 1982;Bell and World Health Organization Writing Group, 2006b), and also with studies that show that hand washing with soap and water is effective in removing pathogens from the surface of the hands (Larson et al, 2003;Luby et al, 2001).…”
Section: Discussionsupporting
confidence: 59%
“…These studies 175,189,196 showed that the action of ABHS against HAV, polio, and rotavirus was significantly better than that achieved by handwashing with soap. However, in the test model used by Ansari et al 189 and Mbithi et al,196 inoculated fingertips are exposed to soap solution or ABHS by inverting them over a vial containing the product. In practice, handwashing involving rubbing and rinsing is likely to remove larger numbers of organisms from hands.…”
Section: Efficacy Of Abhsmentioning
confidence: 99%
“…A number of in vivo studies have been carried out to determine the efficacy of ABHS in reducing the release of viruses from hands. Test methods were variants of the method of Ansari et al 189 or the ASTM E1174 method, 171 in which the virus is applied to the fingertips and the efficacy of the product in reducing the numbers of viral particles recoverable from the hands determined. The residual number of viral particles present on the hands is assessed pre-and posttreatment and the log reduction determined.…”
Section: Efficacy Of Abhsmentioning
confidence: 99%
“…6,10,123,124 Table 4 presents a summary of this information. [125][126][127][128][129][130][131][132][133][134][135] Factors that are considered crucial in the design and performance of tests on the virus-eliminating potential of hygienic hand antiseptics are enumerated in Table 5.…”
Section: Testing Of Handwash and Handrub Agents Against Virusesmentioning
confidence: 99%
“…Also, the topography of inanimate surfaces may be quite different from that of human skin. Whole-hand method Field application of hygienic hand antiseptics can be best simulated in a properly designed whole-hand method, 128 but such methods are inherently more difficult to work with viruses because of the relatively large volumes of inocula required and the eluates to be titrated for infectious virus. Such protocols may be suitable for limited confirmatory testing of hand antiseptics and a standard method is now available for this purpose.…”
Section: Inanimate Carriersmentioning
confidence: 99%